Here, we want to solve the system of linear equations simultaneously
We can start by getting an expression for x from the second equation
We have this as;
[tex]x\text{ = 14-2y}[/tex]We proceed to substitute this into the first equation
We have this as;
[tex]\begin{gathered} 2(14-2y)-6y\text{ = -12} \\ 28-4y-6y=-12 \\ -10y\text{ = -12-28} \\ -10y\text{ = -40} \\ y\text{ = }\frac{-40}{-10} \\ y\text{ = 4} \end{gathered}[/tex]To get the value of x, we simply substitute the y-value into the equation for x
We have this as;
[tex]\begin{gathered} x\text{ = 14-2(4)} \\ x\text{ = 14-8} \\ x\text{ = 6} \end{gathered}[/tex]